A Comparative Evaluation of the Accuracy Between the Extraoral Scanner (Rainbow) and Intraoral Scanner (Medit I500) Digital Impressions( in Vitro) - Ahmed Abduljawad Ismail Alubaidi; Nagham H Kassab; Hasan Khiraldeen Mohialdeen (University of Mosul, College of Dentistry, 2024)
Aims: To compare the extraoral and intraoral scanners' accuracy in obtaining implant impressions using an in-vitro reference model. Materials and methods: An upper master model was fabricated with two parallel dental implants at the first and second premolars missing regions in size (4.0mm in diameter and 10mm in length); twenty impressions were made using the intraoral and extraoral scanners to produce twenty digital impressions (10 for each one), which will result in twenty digital casts. The linear distance measurements were performed using (Medit Design) digital measurement by using Medit Intraoral Scanner. Results: In the digital part there was a highly significant difference between measurements for the oral scanner (MeditI500) and extraoral scanner Rainbow using Medit design, the intra-oral scanner (MeditI500) is the highest value which is at a level of significance p≤0.01. Conclusion: The Medit I500 Intra Oral Scanner is a more accurate impression technique than the Rainbow extraoral scanner in transferring implant position.